Colonial Anxiety and Identity: Ethnic Networks as Cultural Supports in Colonial South Asia and Sumatra - Edward Owen Teggin (Indonesian Historical Studies, 2020)
This study was inspired by research into the personal correspondence of colonial servants in Sumatra and South Asia, and the realisation that their articulation of negative emotions such as anxiety or fear are ill-fitted to the current wider understanding of colonial anxiety. This article argues that the progress of colonial empires was widely shaped by negative emotions such as these, yet there were also methods used by colonial servants to deal with such negative experiences. The core example of this has been the case studies of Robert Cowan and Alexander Hall; these men’s letter archives display their usage of correspondence networks as part of their coping strategy. It is argued that these specifically ethnic, and at times gendered, correspondence networks formed a cultural bulwark which was used to cope with aspects of colonial anxiety. The method of this study therefore was epistolary examination to gather evidence and construct arguments. The archives of Cowan and Hall were compared and examined side by side to identify common patters and content. These were then considered in tandem with the current wider understanding of colonial anxiety. Based on the evidence gathered, it has been concluded that ethnic networks such as those examined could mitigate aspects of colonial anxiety. At the same time, these also demonstrate the great potential for future interdisciplinary studies involving personal histories tied to both Sumatra and South Asia.